Understanding own teaching: becoming reflective teachers through reflective journals. Issue 1 (2nd January 2018) - Zulfikar, Teuku; Mujiburrahman,
Abstract: Reflective journal facilitates teachers to reflect on their teaching and then generate feedback for the improvement of their classroom practices. This study examined how in-service English teachers in a MA Linguistics program at a US Mid-Western University perceived the influence of reflective journals toward their teaching attitudes. At the time of the research, participants were 25 years of age or older. The findings generated from interviews indicated that most participants were convinced that reflective journals help them become reflective teachers. It also found that most in-service teachers regard reflective journals as an effective tool to increase teaching awareness, and thus improve their performance during teaching.